Aplikasi Mobile Untuk Pengelolaan Pengumuman dan Informasi Sekolah Dengan Fitur Push Notification - Aristho Umbu Nggaba Kaho (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
Information technology is one of the important aspects in life, including iin the world of education. In this research, an application for managing school announcements and information with push notification features is developed. The purpose of designing this application is to improve communication between the school, students and parents of students at SMK Negeri 3 Pahunga Lodu. Because this school still uses conventional methods in delivering announcements and information. Through needs analysis, design, development, push notification feature implementation, and application testing, this research succeeded in creating a platform that allows users to receive real-time information. Testing the feasibility of the application using the System Usability Scale (SUS) involving 20 respondents, the score generated in this test is 78. This shows that this application has a good level of usability. the implementation of this application is expected to answer the problems of SMK Negeri 3 Pahunga Lodu.